Verifying the wall-flow-guided assumption of the lateral swirl combustion system in DI diesel engines. (15th April 2020) - Chen, Yanlin; Li, Xiangrong; Li, Xiaolun; Zhao, Weihua; Liu, Fushui
Abstract: A lateral swirl combustion system (LSCS) was designed to promote the spatial spray distribution through the spray wall impingement, and previous studies have established its combustion performance improvement in direct injection (DI) diesel engines. To verify that the improvement in combustion performance is due to the optimal wall-flow-guidance under the assumptive spray impingement position, numerical and experimental tests were conducted under different circumferential injection angles (CIA). The fuel/air mixing and combustion characteristics were computed and analyzed. The endoscopic visualization technique was applied to a single-cylinder diesel engine to record the spray and combustion processes. Based on the two-color method, flame temperature distribution, soot concentration distribution and the corresponding combustion performance were analyzed. Then the variation tendency of combustion performance was further validated under different engine speeds. The numerical and simulation results consistently show that the LSCS chamber and spray jet achieve an optimal match when the spray impingement position is precisely on the convex edge (CIA = 0°). At this position, the LSCS exerts the lowest fuel consumption and soot emission under various engine speeds, because significant lateral swirls form and evenly distribute fuel across all split arcs, promoting the in-cylinder fuel/air mixing and combustion. Therefore, the wall-flow-guided assumption of the LSCS in DI diesel engines is successfully verified in this study.